High‐Performance Planar Heterojunction Perovskite Solar Cells Based on BaCl2 Additive and Power Conversion Efficiency of Over 21%. (9th May 2021) - Zong, Beibei; Zhang, Zizhao; Shun, Qing; Kang, Bonan; Silva, S. Ravi P.; Lu, Ge yu
Abstract: The photoelectric conversion efficiency of perovskite solar cells (PSCs) has rapidly developed in the past decade. However, the development of PSCs still has many limitations: for instance, the accumulation of harmful defects on their surfaces and grain boundaries limit their performance. Here, PSCs with ITO/SnO2 /FA x MA1− x Pb(I y Br1− y )3 /Spiro‐OMeTAD/Ag structure are fabricated under air conditions, meanwhile, the effect the different masses of BaCl2 (0, 10, 15, 20, and 25 mg) added to FA x MA1− x Pb(I y Br1− y )3 perovskite precursor solution on the performance of PSCs is investigated. The results show that the best performance is obtained when 20 mg BaCl2 is added, and the performance parameters J sc, V oc, FF of the PSCs (those with 20 mg BaCl2 ) are 24.43 mA cm −2, 1137 mV, and 75.82, respectively, and their power conversion efficiency is up to 21.06%, which is ≈25% higher than that of the reference devices (those without BaCl2 ). Test results, such as XRD, SEM, TRPL, SCLC, UV–Vis, show that right amount of BaCl2 additive can significantly improve the crystallinity, absorbance, and interface defect state of perovskite films. It can also increase the separation and mobility of charge carriers, thus greatly improving the performance of PSCs. Abstract : PSCs with different masses of BaCl2 additive in the perovskite precursor solution are fabricated under air conditions. The results show that the champion PSC can be obtained when BaCl2 is 20 mg, because it significantly improves the crystallinity, absorbance, and interface defect state of perovskite films. Additionally, the PCE of the device increases from 16.85 to 21.06%.